Leopold's shack and Ricketts's lab : the emergence of environmentalism - Lannoo, Michael J. (University of California Press, 2010)
Leopold's Shack and Ricketts's Lab brings fresh insight to the fertile ideas and writings of two innovators of early twentieth century ecology. In this insightful and important book, Michael J. Lannoo enriches the legacies of Leopold and Ricketts as early conservation-minded environmentalists and suggests that there is still much to be learned from them."Katharine A. Rodger, editor of Breaking Through: Essays, Journals, and Travelogues of Edward F. Ricketts "Lannoo creatively explores an important story of compelling historical characters with a clear vision of their signific